Human Resources Development Policies and Strategies: The Efforts to Strengthen Institutions - Neneng Hasanah; Lias Hasibuan; Kasful Anwar Us (Postgraduate Studies UIN Sulthan Thaha Saifuddin Jambi, 2020)
Abstract: Human resources are one of the most fundamental parts in the development and renewal of a nation. The qualification of human resources will determine whether or not the goals of an institution or institution are achieved. The quality of human resources needs to be developed in order to be able to face competitive social transformations. This article aims to explain the concept of human resources, identification of the value of human resources and human resource development efforts. This article is a library research whose main source is literature on human resources, human resource development strategies and development and reform. Broadly speaking, it can be concluded that strategies are needed in developing human resources so that the quality can be transformed into a more up to date direction. One aspect that can support the process of developing human resources is the aspect of education. Keywords: human resources, development strategy, institutions. Abstrak: Sumber daya manusia merupakan salah satu bagian yang sangat fundamental dalam pembangunan dan pembaharuan suatu bangsa. Kualifikasi sumber daya manusia sangat menentukan tercapai atau tidaknya tujuan suatu institusi ataupun lembaga. Kualitas sumber daya manusia tersebut perlu untuk dikembangkan, supaya mampu menghadapi transformasi sosial yang kompetitif. Artikel ini bertujuan untuk menjelaskan tentang konsep sumber daya manusia, identifikasi nilai sumber daya manusia dan upaya pengembangan sumber daya manusia. Artikel ini merupakan penelitian pustaka yang sumber utamanya adalah literature tentang sumber daya manusia, strategi pengembangan sumber daya manusia serta pembangunan dan pembahuaruan. Secara garis besar dapat disimpulkan bahwa sangat diperlukan strategi-strategi dalam pengembangan sumber daya manusia agar kualitasnya mampu bertransformasi ke arah yang lebih up to date. Salah satu aspek yang dapat menunjang proses pengembangan sumber daya manusia adalah aspek pendidikan. Kata-kata kunci: sumber daya manusia, strategi pengembangan, institusi.